Urban theatricalities, a communicational claim. Reading of the scenic performances of the city of Jijel (Algeria) - Khelfallah, Sheherazad; Farhi, Abdallah (Quaestiones Geographicae, 2021)
This article aims to analyse and interpret the structures responsible for the urban theatricality with deep claims of the city of Jijel (Algeria). It is through scenic readings of public space that this study explores the latent ex- pressions of users as stage directors. This will be done mainly with observation supported by research interviews that combine qualitative and quantitative studies. The urban theatricalities studied in this paper are those unconscious, spontaneous and continual experiences that the actors of the urban scene use to make an urban spectacle. It is about the spectacle of daily life and scenic transcriptions of experiences. The results of this scenic reading of urban script allow us to understand the hidden expressions responsible for communicational theatrical structures.